Radiation instability in a split-cavity resonator - Maroz, Illia V.; Rouba, Anatoly A. (Journal of the Belarusian State University. Physics, 2019)
The interaction of an electron beam with the electromagnetic field of a split resonator that consists of a hollow cylindrical  resonator and a conducting grid dividing it into coupled sections was considered. In the small-signal approximation, taking into account the space charge of the beam for an asymmetric resonator, the expression for the energy loss by the electron passing through the system was obtained. Within the chosen approximation, it was shown that a resonator with equal length sections provides greater efficiency in the transfer of energy from a charged particles beam to an electromagnetic field in comparison with an asymmetric system configuration. It was found that the interaction of an electron with a space charge in a split resonator leads to the increase of the radiation beam instability with the increase of its density. The effect of current modulation of the electron beam passing through the system was studied. It was shown that the resonator size increase leads to the increase of the amplitude of the beam current variable component at the system output. The increase of the current density of the beam entering the interaction region also leads to the increase of the modulation efficiency. The possibility of increasing the modulated current amplitude in a system with unequal sections was considered.
Keywords: electron beam modulation; radiation instability of the beam; space charge; microwave radiation; split-cavity resonator